New and little known geophilomorph centipedes from Amazonian inundation forests near Manaus, Brazil (Chilopoda: Geophilomorpha) - Pereira, Luis Alberto (1994)
Fil: Pereira, Luis Alberto. Facultad de Ciencias Naturales y Museo; Universidad Nacional de La Plata